Dynamics of Fish Import Trade to India – Cross Sectional Analysis of Trade Quantity, Value and Policy Aspects: Dynamics of Fish Import to India: CSA of Trade - C G, Joshy; A, Suresh; Panda, Satyen Kumar; A A, Zynudheen; Ninan, George (Fishery Technology, 2024)
India continues to import fish and fishery products under different harmonized system (HS) codes to meet the domestic and global demand. There have been structural or compositional changes in the import items of fish and fish products during the period 2000-2019. The normalized fish trade balance for quantity and import value was in the rage of 0.92– 0.97 during 2000-2019, which indicated that India is a fish export-oriented country. Even then, the import of fish and fishery products increased linearly during this period at a rate of 1656 tonnes in terms of quantity. India had imported 3232 tonnes of fish and fishery products worth US $4.6 Million in 2000, which increased to 39525 tonnes worth US $112 Million in 2019. The import of chilled form of fish and fishery products under the head HS-0302 decreased during the period 2000-2019, whereas the import of crustaceans under the head HS-0306 increased. But, value wise contribution from items under the head HS – 0304 increased significantly compared to the other heads. Asian countries like Bangladesh, Thailand, Indonesia, Singapore, Malaysia, Vietnam, China, Oman and UAE were the major countries exported fish and fishery products to India under different HS codes. The study highlights India’s fish import policy, focusing on strict sanitary and phytosanitary requirements and a robust market intelligence system, due to high domestic market demand.